2015
DOI: 10.1111/joor.12357
|View full text |Cite
|
Sign up to set email alerts
|

Headache attributed to masticatory myofascial pain: impact on facial pain and pressure pain threshold

Abstract: There is no clear evidence on how a headache attributed to temporomandibular disorder (TMD) can hinder the improvement of facial pain and masticatory muscle pain. The aim of this study was to measure the impact of a TMD-attributed headache on masticatory myofascial (MMF) pain management. The sample was comprised of adults with MMF pain measured according to the revised research diagnostic criteria for temporomandibular disorders (RDC/TMD) and additionally diagnosed with (Group 1, n = 17) or without (Group 2, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…In agreement with these results, previous studies obtained hypoalgesia only in the area where treatment was applied, and in these studies, the participants also presented with more than one disorder. 56,57 However, other studies in which the sample consisted of patients without comorbidities have shown that the application of manual therapy and therapeutic exercises produced generalized hypoalgesia. [58][59][60][61] These results have shown overall positive outcomes for muscle pain, given an increase in PPTs at the anterior temporalis (area of migraine pain) and at the masseter muscle (area of TMD pain).…”
Section: Discussionmentioning
confidence: 98%
“…In agreement with these results, previous studies obtained hypoalgesia only in the area where treatment was applied, and in these studies, the participants also presented with more than one disorder. 56,57 However, other studies in which the sample consisted of patients without comorbidities have shown that the application of manual therapy and therapeutic exercises produced generalized hypoalgesia. [58][59][60][61] These results have shown overall positive outcomes for muscle pain, given an increase in PPTs at the anterior temporalis (area of migraine pain) and at the masseter muscle (area of TMD pain).…”
Section: Discussionmentioning
confidence: 98%
“…Until 2014, the only option to classify secondary headaches was through the guidelines of the International Headache Society fully described in the three versions of the ICHD (7,64,66). However, because of the high co-occurrence of headache and TMD in the clinical practice of oro-facial pain specialists and the extensive research made by dentists in this particular field (4,18,19,32,46,(67)(68)(69)(70)(71)(72)(73)(74), the new DC/TMD, which can be considered the newest 'reference standard' for TMD classification, also proposed criteria to define headache attributed to TMD (17). These criteria discriminate the location of secondary headache only to the temple area and the causation criteria are restricted to the report of familiar headache modified by jaw movement, function or parafunction associated with the clinical provocation of headache.…”
Section: Classificationmentioning
confidence: 99%
“…On the other hand, another study showed that when migraine and TMD coexists, a significant improvement of headache was achieved when both were treated simultaneously (70). However, it seems that the headache attributed to TMD does not interfere with the TMD management in patients with myofascial TMD (67). These data reinforce the importance to differentiate between the type of comorbidity between headaches and TMD and strengthen the recommendation for multidisciplinary approaches, when necessary, focusing on and addressing both conditions, by a team of oro-facial pain specialists and a neurologist (headache specialist).…”
Section: Therapeutic Approaches For Tmd and Primary Headaches Overlapmentioning
confidence: 99%
“…Recent studies suggest that TMDH is amenable to the management of TMD . Patients with TMDH exhibited a significantly increased pressure pain threshold (PPT) in the temporalis muscles, while TMD patients without TMDH had a significantly increased PPT in the masseter muscles . In a study comparing TMD with and without temple headaches, patients with temple headaches had increased TMD pain intensity, increased TMD signs, increased sensitivity in trigeminal and non‐trigeminal sites, greater number of painful sites, and increased headache frequency .…”
Section: Introductionmentioning
confidence: 99%